Enhancement of H2S sensing performance of rGO decorated CuO thin films: experimental and DFT studies. (15th February 2023) - Kumar, Sumit; Chaurasiya, Rajneesh; Khan, Mustaque A; Meng, Gang; Chen, Jen-Sue; Kumar, Mahesh
Abstract: We demonstrate a highly selective and sensitive Cupric oxide (CuO) thin film-based low concentration Hydrogen sulfide (H2 S) sensor. The sensitivity was improved around three times by decorating with reduced graphene oxide (rGO) nanosheets. CuO thin films were deposited by Chemical Vapor Deposition followed by inter-digital electrode fabrication by a thermal evaporations system. The crystal structure of CuO was confirmed by x-ray diffraction. The sensing response of pristine CuO was found around 54% at 100 °C to 100 ppm of H2 S. In contrast, the sensing response was enhanced to 167% by decorating with rGO of 1.5 mg ml −1 concentration solution. The sensing was improved due to the formation of heterojunctions between the rGO and CuO. The developed sensor was examined under various gas environments and found to be highly selective towards H2 S gas. The improvement in sensing response has been attributed to increased hole concentration in CuO in the presence of rGO due to the Fermi level alignment and increased absorption of H2 S molecules at the rGO/CuO heterojunction. Further, electronic structure calculations show the physisorption behavior of H2 S molecules on the different adsorption sites. Detailed insight into the gas sensing mechanism is discussed based on experimental results and electronic structure calculations.